Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015; Session “Brain & Development” - Various Authors, — (Journal of Pediatric and Neonatal Individualized Medicine (JPNIM), 2015)
Selected Abstracts of the 1st Congress of joint European Neonatal Societies (jENS 2015); Budapest (Hungary); September 16-20, 2015 ORGANIZING INSTITUTIONS European Society for Neonatology (ESN), European Society for Paediatric Research (ESPR), Union of European Neonatal & Perinatal Societies (UENPS), European Foundation for the Care of Newborn Infants (EFCNI), with the local host of Hungarian Society of Perinatology and Obstetric Anesthesiology, Hungarian Society of Perinatology (MPT), supported by Council of International Neonatal Nurses (COINN), organizing secretariat MCA Scientific Events PROGRAMME COMMITTEE Artúr Beke (Hungarian Society), Morten Breindahl (ESN), Giuseppe Buonocore (UENPS), Pierre Gressens (ESPR), Silke Mader (EFCNI), Manuel Sánchez Luna (UENPS), Miklós Szabó (Hungarian Society of Perinatology), Luc Zimmermann (ESPR) Session “Brain & Development” ABS 1. SEPARATE EFFECTS OF LOW PATERNAL AND MATERNAL EDUCATIONAL LEVEL ON RISK OF DEVELOPMENTAL DELAY IN 4-YEAR-OLD BOYS AND GIRLS • S. de Jong, M.R. Potijk, A.E. den Heijer, S.A. Reijneveld, A.F. Bos, J.M. Kerstjens ABS 2. THE ASSOCIATION BETWEEN PATERNAL EDUCATIONAL LEVEL AND DEVELOPMENTAL DELAY IN PRETERM AND TERM-BORN CHILDREN AT AGE 4 • S. de Jong, J.M. Kerstjens, A.E. den Heijer, A.F. Bos, S.A. Reijneveld, M.R. Potijk ABS 3. NEUROPROTECTION BY NEURONAL OVEREXPRESSION OF THE SMALL GTPase-Ras IN HYPEROXIA-INDUCED NEONATAL BRAIN INJURY • M. Serdar, K. Kempe, J. Herz, R. Herrmann, B.S. Reinboth, R. Heumann, A. Ehrkamp, U. Felderhoff-Mueser, I. Bendix ABS 4. REFERENCE RANGES FOR CEREBRAL TISSUE OXYGEN INDEX (cTOI) IN NEONATES DURING IMMEDIATE NEONATAL TRANSITION AFTER BIRTH • N. Baik, B. Urlesberger, B. Schwaberger, G. Schmölzer, A. Avian, L. Mileder, G. Pichler ABS 4. REFERENCE RANGES FOR CEREBRAL TISSUE OXYGEN INDEX (cTOI) IN NEONATES DURING IMMEDIATE NEONATAL TRANSITION AFTER BIRTH • N. Baik, B. Urlesberger, B. Schwaberger, G. Schmölzer, A. Avian, L. Mileder, G. Pichler ABS 6. N-ACETYLCYSTEINE AMIDE (NACA) REDUCES CELL DEATH AFTER EXPOSURE TO OXIDATIVE STRESS IN A PORCINE EPITHELIAL-LIKE EMBRYONIC EFN-R KIDNEY CELL LINE • T. Benterud, S. Manueldas, L. Pankratov, R. Solberg, A. Nordgren, O.D. Saugstad, L.O. Baumbusch ABS 7. MELATONIN-INDUCED IMMUNE CELL RESPONSES IN INFANTS WITH NEONATAL ENCEPHALOPATHY PRE AND POST THERAPEUTIC HYPOTHERMIA TREATMENT • S. Aslam, V. McEneaney, R.W.G. Watson, A. O’Neill, E.J. Molloy ABS 8. BLOOD PRESSURE DURING THE IMMEDIATE NEONATES TRANSITION: IS THE MIDDLE ARTERY PRESSURE (MAP) RELEVANT FOR THE REGIONAL CEREBRAL OXYGENATION (crSO2)? • N. Baik, B. Urlesberger, B. Schwaberger, G. Schmölzer, A. Avian, G. Pichler ABS 9. BETWEEN 1993 AND 2012: EVOLUTION OF CEREBRAL PALSY IN PRETERM CHILDREN • M. Bickle Graz, J. Schneider, A.C. Truttmann ABS 10. N-ACETYLCYSTEINE AMIDE (NACA) MAY HAVE NEUROPROTECTIVE PROPERTIES AFTER PERINATAL ASPHYXIA • T. Benterud, L. Pankratov, R. Solberg, A. Nordgren, L.O. Baumbusch, O.D. Saugstad ABS 11. BRAIN INTERSTITIAL PH CHANGES DURING THE SUBACUTE PHASE IN A NEWBORN PIGLET PERINATAL ASPHYXIA MODEL • J. Németh, G. Remzső, V. Tóth-Szűki, F. Domoki ABS 12. NEUROPROTECTIVE EFFECT OF REMIFENTANIL ON EXCITOTOXIC-INDUCED BRAIN DAMAGE IN NEONATAL MICE • C. Chollat, F. Tourrel, M. Lecointre, Y. Ramdani, S. Marret, B. Gonzalez, S. Jégou ABS 13. THE SafeBoosC II TRIAL: REDUCING CEREBRAL HYPOXIA WITHOUT CHANGING EARLY BIOMARKERS OF BRAIN INJURY • A.M. Plomgaard, W. van Oeveren, T.H. Petersen, T. Alderliesten, T. Austin, F. van Bel, M. Benders, O. Claris, E. Dempsey, A. Franz, M. Fumagalli, C. Gluud, C. Hagmann, S. Hyttel-Soerensen, P. Lemmers, A. Pellicer, G. Pic ABS 14. PREDICTING WHITE MATTER DAMAGE BY EVALUATION OF THE LINEAR GROWTH RATE OF CORPUS CALLOSUM IN VERY LOW BIRTH WEIGHT INFANTS • H. Huang, C. Chen, H. Chou, P. Tsao, W. Hsieh ABS 15. REGIONAL AND DEVELOPMENTAL SCREENING OF BILIRUBIN TOXICITY: HIPPOCAMPUS IS THE MOST SENSIBLE REGION • M. Dal Ben, C. Tiribelli, S. Gazzin ABS 16. EFFICACY, SAFETY AND COMORBID EVENTS DURING TRANSPORT OF ASPHYXIATED NEWBORNS TO A TERTIARY CENTRE FOR THERAPEUTIC HYPOTHERMIA • N. Carreras, M. Alsina, G. Arca, M. León, A. García-Alix ABS 17. BRAIN WHITE MATTER INJURY ASSOCIATED WITH NEONATAL SEIZURE AFTER ROTAVIRUS INFECTION • M.J. Kim, S.Y. Byun ABS 18. NOVEL PLASMA AND CEREBROSPINAL FLUID BIOMARKERS OF HYPOXIC-ISCHEMIC ENCEPHALOPATHY IDENTIFIED BY MASS SPECTROMETRY • K.J. Kyng, A. Edhager, C.S. Andreassen, T.B. Henriksen, N. Gregersen, J. Palmfeldt ABS 19. RISK OF HYPOCAPNIA IN ASPHYXIATED NEWBORNS TREATED WITH EARLY THERAPEUTIC HYPOTHERMIA • E. Szakmar, A. Jermendy, A. Nagy, A. Szell, A. Berenyi, B. Bundzsity, A. Cseko, G. Bokodi, D. Kelen, U. Meder, Zs. Somogyvari, M. Szabo ABS 20. INCIDENCE AND RISK FACTORS OF INTRAVENTRICULAR HEMORRHAGE IN INBORN AND OUTBORN INFANTS IN THIRD LEVEL HOSPITALS BEFORE 32 WEEKS OF PREGNANCY • D. Szpecht, M. Szymankiewicz, J. Gadzinowski ABS 21. IMPAIRMENT OF OLIGODENDROGLIAL DEVELOPMENT IN VITRO AT 21% O2 IS ATTENUATED BY STABILIZATION OF HYPOXIA-INDUCIBLE FACTOR 1α • C. Brill, R. Herrmann, C. Bührer, T. Schmitz ABS 22. BODY CORE TEMPERATURE: A NOVEL BIOMARKER FOR HYPOXIC-ISCHAEMIC ENCEPHALOPATHY • D. Jayasinghe, L. Wilcox ABS 23. APGAR SCORES PREDICT ENCEPHALOPATHY MORE THAN BIOCHEMICAL MARKERS • R. Jones, A. Heep, D. Odd ABS 24. REFERENCE VALUES FOR THE NEUROPEPTIDE SECRETONEURIN IN HEALTHY TERM NEWBORNS • A. Schmid, M. Höck, A. Posod, M. Urbanek, R. Fischer-Colbrie, V. Neubauer, U. Kiechl-Kohlendorfer, E. Griesmaier ABS 25. EFFECTS OF VENTILATION ON THE CEREBRAL CORTEX FOLLOWING INTRAUTERINE INFLAMMATION IN PRETERM LAMBS • A. Atik, B. Skiöld, S. Barton, J. Pearson, Q. Wu, V. Zahra, A. Moxham, S. Hooper, M. Tolcos, R. Galinsky, G. Polglase ABS 26. CEREBRAL ULTRASOUND FINDINGS DURING THERAPEUTIC HYPOTHERMIA FOR NEONATAL HYPOXIC-ISCHEMIC ENCEPHALOPATHY: VALIDATION OF A NEW CLASSIFICATION SYSTEM • A. Graca, J. Barreira, C. Santos, C. Moniz ABS 27. A NEW TRANSLATIONAL MODEL OF PERINATAL ASPHYXIA REVEALS LASTING BEHAVIORAL DEFICITS • A. Kerenyi, E. Sipos, P. Bakos, K. Demeter, P. Pottyondi, J. Haller, M. Szabo, K. Kaila, E. Mikics, A. Denes, A. Fekete ABS 28. EFFECT OF EARLY NUTRITION ON PRETERM CEREBRAL MATURATION AND BRAIN INJURY REFLECTED BY MR-IMAGING AT TERM • L. Beauport, J. Schneider, P. Hagmann, M. Faouzi, C.J. Fischer Fumeaux, A.C. Truttmann ABS 29. NEURITE OUTGROWTH IN RESPONSE TO CEREBROSPINAL FLUID DERIVED FROM NEC-SENSITIVE PRETERM PIGS • J. Sun, S. Pankratova, D.E.W. Chatterton, P.T. Sangild ABS 30. URINARY NEUTROPHIL GELATINASE-ASSOCIATED LIPOCALIN (NGAL) AFTER GLOBAL HYPOXIA-ISCHEMIA IN NEWBORN PIGLETS • H.T. Garberg, M.U. Huun, G. Dyrhaug, R. Solberg, O.D. Saugstad ABS 31. CEREBRAL DEEP GREY MATTER ALKALOSIS IN BABIES WITH NEONATAL ENCEPHALOPATHY IS ASSOCIATED WITH AN INCREASED SEIZURE BURDEN • C. Uria-Avellanal, D. Price, M. Sokolska, S. Mitra, A. Bainbridge, X. Golay, N. Robertson ABS 32. THE PROGNOSTIC VALUE OF NIRS DURING THERAPEUTIC HYPOTHERMIA IN TERM ASPHYXIATED NEWBORNS • P. Costa, A. Graça, I. Sampaio, C. Moniz ABS 33. EEG DISCONTINUITY PREDICTS CEREBRAL TISSUE INJURY AND ADVERSE NEURODEVELOPMENT IN COOLED NEWBORNS • J. Dunne, D. Wertheim, P. Clarke, O. Kapellou, P. Chisholm, J. Boardman, D. Shah ABS 34. A RANDOMIZED CONTROLLED TRIAL OF COOLING COMBINED WITH INHALED XENON FOR PERINATAL ASPHYXIAL ENCEPHALOPATHY WITH CEREBRAL MAGNETIC RESONANCE ENDPOINTS – THE TOBY-Xe TRIAL • D. Azzopardi, N. Robertson, A. Bainbridge, E. Cady, A. Deierl, G. Fagiolo, N. Franks, J. Griffiths, J. Hajnal, E. Juszczak, B. Kapetanakis, L. Linsell, M. Maze, O. Omar, B. Strohm, N. Tusor, A.D. Edwards ABS 35. MULTIORGAN DYSFUNCTION IN NEWBORNS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY IN THE HYPOTERMIA ERA • M. Alsina, A. Martin-Ancel, P. Alamillo, M. Leon, A Garcia-Alix ABS 36. HYPOXIC-ISCHAEMIC BRAIN INJURY: DELIVERY BEFORE INTRAPARTUM EVENTS • D. Odd, A. Heep, K. Luyt, T. Draycott ABS 37. IS NEONATAL ESTABLISHED HEARING LOSS PERMANENT IN NICU GRADUATES? • J. Kuiper, W. van Huffelen, R. Benard ABS 38. SHOULD WE CORRECT FOR GESTATIONAL AGE WHEN ASSESSING DEVELOPMENT IN PRETERM-BORN CHILDREN? • N.H. van Dokkum, J.M. Kerstjens, D.M. van Maanen, A.F. de Winter, A.F. Bos, S.A. Reijneveld ABS 39. NEUROCOGNITIVE DISABILITIES IN CHILDREN WITH MINOR NEUROLOGICAL DYSFUNCTION BORN VERY PRETERM • T. Kurpershoek, E. Potharst-Sirag, C. Aarnoudse-Moens, A. van Wassenaer-Leemhuis ABS 40. 2 YEAR NEURODEVELOPMENTAL OUTCOMES FOLLOWING EXTREME PREMATURITY OR EXTREMELY LOW BIRTH WEIGHT IN NOTTINGHAM, UNITED KINGDOM. BIRTH COHORT 2000-2008 • C. Forster, T. Crosby, J. Dorling ABS 41. MONOCHORIONIC DIAMNIOTIC TWINS: A 2-YEAR DEVELOPMENTAL OUTCOME • E. Teixeira, M. Machado, L.M. Ferreira, F. Rodrigues, R. Henriques, E. Afonso ABS 42. EPILEPSY IN CHILDREN BORN MODERATELY AND LATE PRETERM • M. Hirvonen, R. Ojala, P. Korhonen, P. Haataja, K. Eriksson, M. Gissler, T. Luukkaala, O. Tammela ABS 43. SPATIAL LEARNING AND MEMORY IN PRETERM PIGS • A.D. Andersen, L. Langhorn, P.T. Sangild, T. Thymann ABS 44. IS DELAYED NORMALISATION OF PLASMA LACTATE IN COOLED BABIES WITH HYPOXIC-ISCHAEMIC ENCEPHALOPATHY ASSOCIATED WITH A POOR OUTCOME? • N. Ide Bergamaschi, P. Clarke ABS 45. HEAD GROWTH AND NEURODEVELOPMENTAL OUTCOME AT 1 YEAR FOLLOWING FETAL GROWTH RESTRICTION • M. Boyle, R. Pinnamaneni, J. Unterscheider, F. Malone, N. McCallion, A. Foran ABS 46. EEG SLEEP SLOW WAVE ACTIVITY AS A POTENTIAL MARKER OF LOAD-DEPENDENT DEFICITS IN EXECUTIVE FUNCTIONS IN VERY PRETERM CHILDREN AND ADOLESCENTS • F. Wehrle, B. Latal, R. O’Gorman, C. Hagmann, R. Huber ABS 47. EFFECT OF SHORTER DELAY TIME AFTER SUCROSE ADMINISTRATION TO REDUCE HEEL STICK RELATED PAIN IN NEWBORN INFANTS • N.J. Meesters, M. van Dijk, S.H.P. Simons ABS 48. IS MANAGING PAIN A PAIN? NATIONAL SURVEY ON NEONATAL PAIN MANAGEMENT IN THE UNITED KINGDOM • S. Bhayat, H. Gowda ABS 49. INSULIN-LIKE GROWTH FACTOR-1 PROTEIN CONCENTRATION INCREASES PERINATALLY AND REMAINS HIGH POSTNATALLY IN LAMBS, MIRRORING THE PROFILE IN HUMANS FROM THE FOETUS TO THE ADOLESCENT • M. Dahl, D. Keefe, J.-K. Chung, N. Barton, R. Ward, K. Albertine ABS 50. PRETERM INFANTS BORN WITH PRENATAL ABSENT OR REVERSED END-DIASTOLIC FLOW VELOCITY (AREDV) SHOW SIGNIFICANT LOWER BAYLEY III SCALES AT 2 YEARS – A MATCH CONTROL STUDY • C.N. Chen, H.C. Huang, C.Y. Chen, H.C. Chou, W.S. Hsieh, P.N. Tsao ABS 51. OCCURRENCE OF ABNORMAL PLACENTAL HISTOLOGY FINDINGS IN TERM ASPHYXIATED INFANTS • A.I. Tóth, M. Szabó, Á. Nándor, E. Széll ABS 52. THE ANTISECRETORY FACTOR IN PRETERM AND TERM PLACENTAS • A. Gustafsson, E. Fransson, A. Dubicke, S.A. Silfverdal, E. Jennische, S. Lange, K. Bohlin ABS 53. PRENATAL EXPOSURE TO HYDROXYLATED POLYCHLORINATED BIPHENYLS IS ASSOCIATED WITH MENTAL AND MOTOR DEVELOPMENT OF INFANTS AT THE AGE OF 18 MONTHS • M. Ruel, A. Bos, S. Soechitram, L. Meijer, P. Sauer, S. Berghuis ABS 54. DEVELOPMENT OF STRUCTURED REPORTING FOR MRI IMAGES OF NEONATES WITH PERINATAL ASPHYXIA • M. Kolossváry, A. Lakatos, Z. Bagyura, L.R. Kozák, M. Szabó, P. Maurovich-Horvat, G. Rudas ABS 55. THE THERMAL SAFETY OF NEONATAL MAGNETIC RESONANCE BRAIN IMAGING AT 3.0 TESLA • P. Cawley, K. Few, R. Greenwood, P. Malcolm, G. Johnson, P. Lally, S. Thayyil, P. Clarke ABS 56. STRUCTURED REPORTING IN HYPOXIC-ISCHEMIC ENCEPHALOPATHY – BENEFICIAL FOR THE RADIOLOGIST AND THE CLINICIAN • A. Lakatos, M. Kolossvary, M. Szabo, M. Kiss, G. Gyebnar, Z. Bagyura, G. Rudas, L.R. Kozak ABS 57. DIFFUSE OPTICAL IMAGING OF RESTING STATE FUNCTIONAL CONNECTIVITY IN INFANTS • C.W. Lee, R.J. Cooper, L.A. Dempsey, M. Chalia, S. Brigadoi, N. Everdell, J.C. Hebden, T. Austin ABS 58. IN VIVO ASSESSMENT OF CEREBRO-CEREBELLAR CONNECTIVITY IN THE DEVELOPING BRAIN USING HIGH ANGULAR RESOLUTION DIFFUSION IMAGING • K. Pieterman, D. Batalle, J. Dudink, D. Tournier, E. Hughes, N. Tusor, A.D. Edwards, F. Hoebeek, S.J. Counsell ABS 59. TRIGEMINAL ODOURS RELEASED BY HEALTH CARE PRODUCTS ACTIVATE CORTICAL PAIN PROCESSING AREAS AND TRIGGER PAIN BEHAVIOUR IN PRETERM AND FULL TERM BORN INFANTS • J. Frie, M. Bartocci, H. Lagercrantz, P. Kuhn ABS 60. PERSISTENT HYPOMETHYLATION OF THE PRETERM PIG INTESTINE • X. Pan, F. Gao, T. Thymann, P. Sangild ABS 61. EEG BACKGROUND ACTIVITY AND SEIZURE BURDEN ARE ASSOCIATED WITH BRAIN INJURY ON MRI AND NEURODEVELOPMENTAL OUTCOME IN FULL-TERM INFANTS WITH HYPOXIC-ISCHAEMIC ENCEPHALOPATHY • L. Weeke, G. Boylan, R. Pressler, B. Hallberg, F. Groenendaal, L. de Vries ABS 62. NEURODEVELOPMENTAL DISABILITIES AND SPECIAL HEALTH CARE NEEDS AT 12 YEARS IN CHILDREN BORN AT < 26 WEEKS’ GESTATION AFTER ACTIVE PERINATAL CARE • A. Farooqi, A. Holsti, B. Hägglöf, M. Adamsson, F. Serenius ABS 63. PARENT AND NURSE PERSPECTIVES ON PARENTAL PARTICIPATION AND SUPPORT IN 11 EUROPEAN NICUs • A. Axelin, S. Raiskila, B. Westrup, B. Silnes Tandberg, L. Lehtonen; SCENE research group ABS 64. INCIDENCE OF FOCAL PRETERM BRAIN INJURY IN A DUTCH CENTER SPECIALIZED IN TREATMENT OF EXTREMELY PRETERM BIRTH • R. de Goederen, R. de Jonge, P. Govaert, M. Feijen-Roon, I. Reiss, J. Dudink ABS 65. PREDICTION OF NEURODEVELOPMENTAL OUTCOME IN INFANTS WITH INTRAVENTRICULAR HEMORRHAGE USING A FUNCTIONAL MRI SCORE • K. Goeral, G. Kasprian, C. Leeb, R. Fuiko, A. Berger, M. Olischar, K. Klebermass-Schrehof ABS 66. SYSTEMIC HEMOLYSIS AND HYPEROXEMIA IN A RAT PUP MODEL; A NOVEL WAY OF MODELING EFFECTS OF CARDIOPULMONARY BYPASS • Å. Jungner, S. Vallius, M. Gram, D. Ley ABS 67. BRAIN INJURY AND NEUROLOGICAL DEFICITS IN DIFFERENT MODELS OF HYPOXIA-ISCHEMIA IN NEONATAL MICE • B.S. Reinboth, C. Köster, K. Strasser, I. Bendix, U. Felderhoff-Müser, J. Herz ABS 68. COLD-INDUCIBLE RNA BINDING PROTEIN RBM3 PREVENTS ENDOPLASMIC RETICULUM (ER) STRESS-INDUCED APOPTOSIS • X. Zhu, A. Zelmer, J. Kapfhammer, S. Wellmann ABS 69. NEUROINFLAMMATION, A KEY FACTOR IN THE PATHOPHYSIOLOGY OF PRETERM INTRAVENTRICULAR HEMORRHAGE: THE ROLE OF MICROGLIA CELLS AND HAPTOGLOBIN AS A FEASIBLE THERAPY • A. Agyemang, S. Vallius, D. Ley, M. Gram ABS 70. FINGOLIMOD REDUCES NEONATAL WHITE MATTER DAMAGE AND LONG-TERM COGNITIVE DEFICITS • I. Bendix, M. Serdar, K. Kempe, J. Herz, K. Lumpe, B.S. Reinboth, S.V. Sizonenko, X. Hou, R. Herrmann, M. Hadamitzky, R. Heumann, M. Sifringer, Y.v.d. Looji, U. Felderhoff-Müser ABS 71. NEURODEVELOPMENTAL OUTCOME AFTER EARLY HIGH DOSE RECOMBINANT HUMAN ERYTHROPOIETIN IN VERY PRETERM INFANTS: RESULTS OF A RANDOMIZED PLACEBO-CONTROLLED, DOUBLE-BLIND TRIAL • G. Natalucci, B. Latal, B. Koller, C. Rüegger, B. Sick, L. Held, H.U. Bucher, J.C. Fauchère; on behalf of the ‘The Swiss EPO Neuroprotection Trial Group’ ABS 72. THE HEME AND RADICAL SCAVENGER α1-MICROGLOBULIN (A1M) CONFERS PROTECTION OF THE PERIVENTRICULAR WHITE MATTER FOLLOWING PRETERM INTRAVENTRICULAR HEMORRHAGE • S. Rutardottir, S. Sveinsdottir, S.R. Hansson, B. Åkerström, D. Ley, M. Gram ABS 73. VALIDATION OF CEREBRAL NIRS OXIMETRY IN NEWBORN PIGLETS • M. Rasmussen, V. Eriksen, S. Hyttel-Sorensen, G. Greisen ABS 74. BRAIN INJURY IN THE INTERNATIONAL MULTICENTRE RANDOMISED SafeBoosC PHASE II FEASIBILITY TRIAL: CRANIAL ULTRASOUND AND MAGNETIC RESONANCE IMAGING ASSESSMENTS • A.M. Plomgaard, C. Hagmann, T. Alderliesten, T. Austin, F. van Bel, O. Claris, E. Dempsey, A. Franz, M. Fumagalli, C. Gluud, G. Greisen, S. Hyttel-Soerensen, P. Lemmers, A. Pellicer, G. Pichler, M. Benders ABS 75. DELAYED CORD CLAMPING AT BIRTH IMPROVES MOTOR SCORES AT 18 TO 22 MONTHS CORRECTED AGE: A RANDOMIZED CONTROLLED TRIAL • J. Mercer, D. Erickson-Owens, B. Vohr, R. Tucker, W. Oh, J. Padbury ABS 76. VOICE OUTCOMES FOLLOWING VERY PRETERM BIRTH • S. Meldrum, K. Simmer, S. Vijayasekaran, N. French ABS 77. TIMING OF AMPLITUDE-INTEGRATED ELECTROENCEPHALOGRAPHY RECORDING FOR PREDICTION OF OUTCOME IN PREMATURE INFANTS • E. Ralser, V. Neubauer, U. Pupp-Peglow, U. Kiechl-Kohlendorfer, E. Griesmaier ABS 78. BAYLEY SCALES OF INFANT AND TODDLER DEVELOPMENT (EDITION 3) IN A LOW RISK HEALTHY POPULATION • C. Ahearne, G. Hannon, M. Kiely, L. Kenny, J.O’B. Hourihane, D. Murray ABS 79. EARLY POSTNATAL HYDROCORTISONE IMPAIRS CEREBELLAR GROWTH AND DELAYS NEONATAL AROUSAL IN PRETERM PIGS • A. Brunse, P. Worsøe, M. Birck, P. Sangild ABS 80. ALTERED SLEEP SPINDLE ACTIVITY MAY REFLECT IMPAIRED THALAMOCORTICAL CONNECTIVITY IN VERY PRETERM CHILDREN AND ADOLESCENTS • F. Wehrle, B. Latal, R. O’Gorman, C. Hagmann, R. Huber ABS 81. REGIONAL CEREBRAL OXYGENATION AS MEASURED BY NEAR-INFRARED SPECTROSCOPY (NIRS) IS RELATED TO NEURODEVELOPMENTAL OUTCOME AT 2 YEARS OF AGE • T. Alderliesten, I.C. van Haastert, W. Baerts, N.E. van der Aa, L.S. de Vries, C. Koopman, F. van Bel, P.M.A. Lemmers ABS 82. A 3D MAP OF ISCHEMIC STROKE FREQUENCY IN THE NEONATAL BRAIN • C. Stephan-Otto, G. Arca-Diaz, A. Garcia-Alix ABS 83. CONGENITAL HEART DISEASE AND INDICES OF FETAL CEREBRAL GROWTH IN A NATIONWIDE COHORT OF 931,174 LIVEBORN INFANTS • N.B. Matthiesen, T.B. Henriksen, J.W. Gaynor, P. Agergaard, C.C. Bach, V. Hjortdal, J.R. Ostergaard ABS 84. CONGENITAL HEART DISEASE, PLACENTAL ANOMALIES AND INDICES OF FETAL GROWTH IN A NATIONWIDE COHORT OF 931,174 LIVEBORN INFANTS • N.B. Matthiesen, T.B. Henriksen, J.W. Gaynor, P. Agergaard, C.C. Bach, V. Hjortdal, J.R. Ostergaard ABS 85. RELATIONSHIP BETWEEN DIFFUSION TENSOR IMAGING AND FINE MOTOR FUNCTION IN YOUNG ADULTS BORN WITH VERY LOW BIRTH WEIGHT • K.A.I. Evensen, I.M. Husby, A. Olsen, J. Skranes, A.M. Brubakk, A.K. Håberg, L. Eikenes ABS 86. INCIDENTAL FINDINGS ON ROUTINE MRI SCANS IN VLBW BABIES: SHOULD WE EXPECT THE UNEXPECTED? • M. Malova, A. Parodi, M. Severino, G. Morana, A. Rossi, A. Sannia, L.A. Ramenghi ABS 87. NEUROIMAGING IN PRESUMED PERINATAL ARTERIAL ISCHEMIC STROKE AND RECOGNITION OF SPECIFIC NEURORADIOLOGICAL PATTERN: A SINGLE CENTER EXPERIENCE • M. Bertamino, M. Severino, M. Di Rocco, A. Rossi, L. Ramenghi; Stroke Group* • *V. Capra, I. Ceccherini, M.E. Celle, C. Gandolfo, A.C. Molinari, A. Palmieri, M. Pavanello, P. Picco, S. Renna, A. Rossi, R. Ravazzolo ABS 88. PUNCTATE WHITE MATTER LESIONS: CORRELATION TO GESTATIONAL AGE AND SWI APPEARANCE • M. Malova, A. Parodi, M. Severino, G. Morana, A. Sannia, A. Rossi, L.A. Ramenghi ABS 89. PREDICTING SCHOOL-AGE COGNITIVE CAPACITIES FROM THE NEONATAL CONNECTOME IN PRETERM BORN CHILDREN • K. Keunen, M.J.N.L. Benders, A. Leemans, I.C. van Haastert, P.C. Fieret-Stam, L.H. Scholtens, M.A. Viergever, R.S. Kahn, F. Groenendaal, L.S. de Vries, M.P. van den Heuvel ABS 90. CORPUS CALLOSUM-FASTIGIUM LENGTH; A NEW SONOGRAPHIC MARKER FOR PRETERM BRAIN GROWTH • J.A. Roelants, I.V. Koning, M.M.A. Raets, S.P. Willemsen, I.K.M. Reiss, M.J. Vermeulen, P. Govaerts, J. Dudink